Analisis Kebijakan Pengembangan Kompetensi Pegawai di Indonesia - Anwaruddin, Awang (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2006)
The issue on the need for developing the competency of Indonesia apparatus appeared when the government found difficulties to overcome the multi-dimension crisis by the dawn of the last century. To implement it, the government published Law Number 43/1999 as the change of Law apparatus competency as professional, neutral, clean from corruption, collution, and nepotism, and having a unity and nation perception. A year later, the government published the competencies needed for various positions in the government institution which are significant for formulating the curricula of competency based development programs-except the Standard of General Cometencies for Structural Officials published in 2001. Such ambiguity impacts on the ineffectivity of cometency development process in Indonesia.